Control, optimization, and management of vehicle electrification in modern power grids - Monteiro, Vítor Duarte Fernandes (2024)
This book chapter, about control, optimization, and management of vehicle electrification in modern power grids demonstrates the key future possibilities of using electric mobility for offering new functionalities and management opportunities for smart grids, as well as in smart homes. Some of the possibilities are well known and studied in literature, and some research projects were already performed or are ongoing, however, other possibilities have not yet been discussed, neither were implemented, constituting a huge opportunity for the advance of vehicle electrification and smart grids. Such possibilities are discussed, and it is demonstrated that their adoption contributes to consider electric mobility as an asset for modern power grids. Thus, in addition to the well-known grid-to-vehicle (G2V) operation mode, where the electric mobility is passive from the power grid point of view, and the also known vehicle-to-grid (V2G) mode, where the electric mobility is active from the power grid point of view, delivering power back to the grid in specific schedules, new possibilities are discussed, such as the modes home-to-vehicle (H2V), vehicle-to-home (V2H), and vehicle-for-grid (V4G), which can be framed in the perspective of smart homes interfacing modern power grids, as well as the direct interface of electric mobility with modern power grids. Along with this book chapter, the possibilities are detailed discussed, and exemplificative experimental results are presented for a developed 3.6 kW bidirectional battery charger prototype.